DEFISIT APBN DAN PEMULIHAN EKONOMI PASCA KRISIS - Haryo Kuncoro (Media Ekonomi, 2012)
Governments play an important role in an economy. The role is presented by both its revenue and expenditure. The net difference of the revenue and expenditure, therefore, determines the type of fiscal policy implementation. This research attempts to analyze the impact of deficit fiscal policy on the private expenditure in the case of Indonesia over the postcrisis 2000-09 periods. The analysis is based on the goods market equilibrium. The approach is designed to analyze whether the government expenditure crowds out the private expenditure. In order to reach the objective of the study, I used the Almost Ideal Demand System (AIDS) and compared to the Generalized Almost Ideal Demand System (GAIDS). The estimation result of quarterly data shows that the government expenditure did not crowd out the private expenditure. The crowding out only occurs partially especially on the private investment. However, the government expenditure totally remains stimulating the private expenditures. This, in turn, leads to increase the gross domestic product. Those results indicate that the expansionary fiscal policy effectively affects to the economic growth especially after economic crisis in 1997. Even, the income elasticity was much greated than that in the precrisis periods. Furthermore, to keep the moment of sustainable economic growth in the long term, the government should conduct discipline fiscal policy based on the prudent principles and coordination and consistency between fiscal and monetary controls.Keywords: Deficit, consumption, investment, government expenditure, crowding out